Racial and ethnic disparities in social engagement among US nursing home residents - Li, Yue (2014)
BACKGROUND: The numbers and proportions of racial and ethnic minorities have increased dramatically in U.S. nursing homes in recent years. Concerns exist about whether nursing homes can serve appropriately the clinical and psychosocial needs of patients with increasingly diverse ethnic and cultural backgrounds. This study determined racial and ethnic disparities in social engagement among nursing home long-term residents. METHODS: We analyzed the 2008 national Minimum Data Set supplemented with the Online Survey, Certification, and Reporting File and the Area Resource File. We estimated multivariable logistic regressions to determine disparities and how disparities were explained by individual, facility, and geographic factors. Stratified analyses further determined persistent disparities within patient and facility subgroups. RESULTS: Compared to white residents (n=690,228), black (n=123,116), Hispanic (n=37,099) and other (n=17,568) residents showed lower social engagement, with overall scores (mean±SD) being 2.5±1.7, 2.2±1.6, 2.0±1.6, and 2.1±1.6, respectively. Disparities were partially explained by variations in individual, facility and geographic covariates, but persisted after multivariable adjustments. Stratified analyses confirmed that disparities were similar in magnitude across patient and facility subgroups. CONCLUSIONS: Although nursing home residents showed overall low social engagement levels, racial/ethnic minority residents were even less socially engaged than white residents. Efforts to address disparities in psychosocial well-being and quality of life of nursing home residents are warranted.